2021
DOI: 10.1007/s41134-021-00162-4
|View full text |Cite
|
Sign up to set email alerts
|

Human Rights of Forced Migrants During the COVID-19 Pandemic: An Opportunity for Mobilization and Solidarity

Abstract: The question of human mobility is inextricably tied to the COVID-19 pandemic that started in late 2019 and whose effects continue to unfold. Human mobility-especially with global advances in transportation and interconnectedness-is an important factor in the spread of the pandemic. Yet, the impact of the COVID-19 pandemic on the millions of people forced to migrate for safety and economic reasons has received little attention. In this article, we provide an overview of human rights challenges that forced migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…However, some countries implemented inclusive policies, such as Portugal's decision to grant full citizenship rights to all migrants and refugees for the duration of the pandemic to ensure that they could freely access health care, testing, and vaccinations. The Spanish government also implemented openness policies, releasing detainees from migrant detention centers to mitigate the risk of the COVID-19 infection (17). These kinds of decisions remained an exception, as most European countries used the pandemic to provide reasons for increased border controls and exclusionary measures targeting refugees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some countries implemented inclusive policies, such as Portugal's decision to grant full citizenship rights to all migrants and refugees for the duration of the pandemic to ensure that they could freely access health care, testing, and vaccinations. The Spanish government also implemented openness policies, releasing detainees from migrant detention centers to mitigate the risk of the COVID-19 infection (17). These kinds of decisions remained an exception, as most European countries used the pandemic to provide reasons for increased border controls and exclusionary measures targeting refugees.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, considering the sometimeslimited resources made available and the transnational dimension of the phenomenon, the need emerges for wider initiatives for migrants' rights and inter-agency cooperation among international organizations (1,16). The migration phenomenon has been inevitably affected by the situation determined by the still ongoing, though reduced, COVID-19 pandemic (17). The impact of the COVID-19 pandemic on millions of migrants received relatively limited attention, although the migration phenomenon did slow down during the pandemic (10).…”
Section: Introductionmentioning
confidence: 99%
“…But it was quickly shown that the contrary was in fact true and that Covid‐19 and the subsequent measures put in place to contain the pandemic had far worse impacts on those who were already marginalised in society through the intersection of racialised and gendered structures of inequality and violence, including refugees (Crawley, 2021). There were some glimpses of hope for improvement in the conditions for refugee reception, such as Portugal's decision to grant full citizenship rights to all migrant and refugees for the duration of the pandemic in order to ensure that they could freely access healthcare, testing and vaccination, or the Spanish government's decision to release detainees from migrant detention centres where they were at risk of catching Covid‐19 (Libal et al ., 2021), and these policies showed that there are other less securitized means of promoting health without marginalising migrant and refugee populations. However, these types of decisions unfortunately remained the exception as most EU States used the pandemic to justify tightening border controls and exclusionary measures aimed at refugees.…”
Section: Discussionmentioning
confidence: 99%
“…La cuestión de la relación entre solidaridades intergrupales y grupales ha sido desde antes un importante foco de atención, ya que un exagerado acento en un sentido de la solidaridad intragrupal, podría debilitar una solidaridad intergrupal, cuestión sensible para grupos en situación minoritaria y vulnerable (Banting y Kymlicka, 2017). Ante la COVID-19, se han demostrado como necesarias, pero también críticas, la solidaridad de las elites económicas hacia el resto de la población (Bobzien y Kalleitner, 2021), y hacia grupos determinados como la población migrante (Libal, 2021), ante el racismo (Cipriano et al, 2020) o hacia la tercera edad (Ayalon et al 2020). Federico et al (2020) encontraron que un alto sentido de la membresía grupal valorado en sí mismo, sería un buen predictor de la solidaridad en la pandemia; mientras que una identificación narcisista con un grupo inhibiría la solidaridad intergrupal.…”
Section: La Solidaridad Y La Covid-19unclassified